1985
DOI: 10.1002/tcm.1770050203
|View full text |Cite
|
Sign up to set email alerts
|

The embryotoxicity of cyclophosphamide in rabbits during the histiotrophic phase of nutrition

Abstract: After iv injection of cyclophosphamide (CP; 80 mg/kg) and dechlor-CP (60 mg/kg) on the 9th day of gestation (histiotrophic phase of nutrition) in rabbits, the concentrations of activated CP and activated dechlor-CP were determined fluorometrically in the maternal blood and in the yolk sac fluid. Activated CP and dechlor-CP could be measured in the maternal blood but not in the yolk sac fluid. This holds true for both the free as well as the protein bound form. During the histiotrophic phase of nutrition on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The visceral yolk sac is involved in the placental functions until just before parturition in rodents and rabbits, as the inverted yolk sac placenta 2 , 33 . CPA inhibits the absorptive activity of the endoderm of the visceral layer of the yolk sac placenta, which may lead to quantitative and/or qualitative nutritional changes in the developing embryos of rabbits 34 . In contrast, in rat embryo culture, phosphoramide mustard is reported to induce DNA fragmentation in the embryos but not in the yolk sac 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The visceral yolk sac is involved in the placental functions until just before parturition in rodents and rabbits, as the inverted yolk sac placenta 2 , 33 . CPA inhibits the absorptive activity of the endoderm of the visceral layer of the yolk sac placenta, which may lead to quantitative and/or qualitative nutritional changes in the developing embryos of rabbits 34 . In contrast, in rat embryo culture, phosphoramide mustard is reported to induce DNA fragmentation in the embryos but not in the yolk sac 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have utilized toxicological and pharmacological agents to modify RME [40], however, relatively few studies have demonstrated a link between toxicological or pharmacological agents and disruption of HNPs during development [35, 4148]. These previous studies encompass a wide range of chemical agents, with diverse structures and functions, and yet many of these exposures have the same outcomes.…”
Section: Discussionmentioning
confidence: 99%